Antioxidant activity and acute toxicity of a recipe used in traditional medicine for the treatment of high blood pressure - NAZAIRE KOMENAN AMANI,; KONAN KOUASSI,; RITA BOUAGNON,; PHILIPPE ALAIN DIT BIDIE,; JOSEPH ALLICO DJAMAN,; DAVID JEAN N'GUESSAN, (International Journal of Phytomedicine, 2015)
The use of recipes using herbs in the treatment of high blood pressure is quite common in Cote d’Ivoire. Among these recipes, a decoction of a mixture of plants called “Tanopati” is one of the most commonly used. The objective of this study is to determine the chemical constituents, evaluate the in vitro antioxidant activity and acute toxicity in mice of lyophilized extract of “Tanopati” recipe. The phytochemical constituents of ‘Tanopati” was determined by the use of common tests related to flavonoids, tannins, leuco- anthocyanins, anthracenosids, terpenoids, steroid and saponins. We have also quantified the total polyphenolics compounds by Folin-Ciocalteu reagent, flavonoids by aluminum trichloride reagent and condensed tannins by a method using iron trichloride. Antioxidant activity was assessed by DPPH test and an acute toxicity test was performed in mice for the determination of Letal dose 50 (LD 50) of “Tanopati”. The phytochemical screening revealed the presence of flavonoids, tannins, leuco-anthocyanin, anthracenosids, terpenoids, steroid and saponins. The quantitative determination of total polyphenols (232 µg EGA/mg), total flavonoids (58.48 µg EQ/mg) and condensed tannins (80,5 µg EC/mg ) showed that “Tanopati” contained a significant amount of phenolic compounds. The reduction of DPPH radicals (IC50= 28 µg/mL) and the capacity to reduce ferric ions to ferrous ions showed a considerable antioxidant activity of “Tanopati”. Acute toxicity study carried out on “Tanopati” performed in mice (p.o.) showed that the recipe is not toxic (LD50˃2000 mg/kg B.W). These results support the safely use of “Tanopati” as a traditional medicine for the care of hypertension. The antioxidant properties are undoubtedly an additional benefit for the usage of “Tanopati” as an antihypertensive drug.